Instability-induced crystal self-assembly in film-substrate system for the construction of large-area micro- and nano-chiral structures - Fushuai Wang; Quanzi Yuan; Xinghua Shi (Nature Communications)
Abstract Chiral supramolecular self-assembly structures demonstrate properties far surpassing achiral counterparts, with broad applications in optoelectronics, biomedicine, and interfaces. However, controlled construction of mesoscopic/macroscopic chiral structures remains challenging due to limited understanding of chirality generation and cross-scale transmission mechanisms. Here, we report an instability-induced crystal self-assembly (IICSA) method where mechanical disturbances trigger structural instability in ibuprofen films, transforming disordered states into large-area ordered chiral structures featuring lamella and left-/right-handed fiber combinations through textured grain stacking. Based on the two-dimensional film model, direct visualization and active control of self-assembly dynamics are realized. Experimental and theoretical analyses reveal how surface/interface effects, geometry effects, and solid-liquid interactions collectively govern the self-assembly dynamics. These chiral structures further demonstrate programmable wettability modulation for surface engineering applications. This study deciphers mechanisms of supramolecular chirality generation and cross-scale transmission while providing a controllable paradigm for constructing mesoscopic/macroscopic chiral systems, advancing functional chiral material design.